Open-Label Placebo Treatment for Acute Postoperative Pain (OLP-POP Study): Study Protocol of a Randomized Controlled Trial - Sezer, Dilan; de Leeuw, Matthijs; Netzer, Cordula; Dieterle, Markus; Meyer, Andrea; Buergler, Sarah; Locher, Cosima; Ruppen, Wilhelm; Gaab, Jens; Schneider, Tobias (Frontiers in Medicine, 2021)
Introduction: Open-label placebos have been proposed as way of using long recognized analgesic placebo effects in an ethical manner. Recent evidence shows efficacy of open-label placebos for clinical conditions, but there is need for more research on open-label placebos in acute pain. In the treatment of acute postoperative pain, minimization of opioid related side effects remains one of the key challenges. Therefore, this study aims at investigating the potential of adding unconditioned open-label placebos to treatment as usual as a means of reducing opioid consumption and its related side effects in patients with acute postoperative pain. Methods and Analysis: This is the protocol of an ongoing single site randomized controlled trial. The first patient was enrolled in May 2020. In total, 70 patients suffering from acute postoperative pain following dorsal lumbar interbody fusion are randomized to either a treatment as usual group or an experimental intervention group. The treatment as usual group consists of participants receiving a patient-controlled morphine pump. On day one and day two post-surgery, patients in the intervention group receive, in addition to treatment as usual, two open-label placebo injections per day along with an evidence-based treatment rationale explaining the mechanisms of placebos. The primary outcome is measured by means of self-administered morphine during day one and two post-surgery. Several other outcome measures including pain intensity and adverse events as well as potential predictors of placebo response are assessed. Analysis of covariance will be used to answer the primary research question and additional statistical techniques such as generalized linear mixed models will be applied to model the temporal course of morphine consumption. Discussion: This study will provide valuable insights into the efficacy of open-label placebos in acute pain and will potentially constitute an important step towards the implementation of open-label placebos in the clinical management of acute postoperative pain. In addition, it will shed light on a cost-efficient and patient-centered strategy to reduce opioid consumption and its related side effects, without any loss in pain management efficacy.